Hospitalization mortality and associated risk factors in patients with polymyositis and dermatomyositis: A retrospective case-control study - Wu, Chanyuan; Wang, Qian; He, Linrong; Yang, Enhao; Zeng, Xiaofeng (PloS one, 2018)
Polymyositis and dermatomyositis (PM/DM) are systemic autoimmune diseases with multiple organ involvements that manifest as muscular and cutaneous disorders, interstitial lung disease (ILD) and malignancies. However, information concerning the outcomes and associated factors for PM/DM patients who are hospitalized is limited. We retrospectively reviewed the medical charts of PM/DM patients admitted to a Chinese tertiary referral hospital (Peking Union Medical College Hospital, PUMCH) from 2008 to 2014. The deceased group included 63 patients who had "deceased discharge" status or were confirmed to have died within two weeks of hospital discharge. The demographic data, clinical manifestations, and direct causes of death were analyzed retrospectively. Medical records for 126 age- and sex-matched PM/DM patients were selected as controls from 982 inpatients successively admitted to the same center during the same period. In addition to the comparison of clinical manifestations between the two groups, binary logistic regression was conducted to explore the risk factors related to PM/DM mortality. Over the past 6 years at PUMCH, the in-hospital mortality rate of PM/DM patients was 4.58%. The male gender and the elder patients had a high risk of death (P = 0.031 and P = 0.001 respectively). The three most frequent causes of death for PM/DM patients were pulmonary infection (35%), ILD exacerbation (21%) or both conditions (25%). Pulmonary infection (P<0.001, OR = 5.63, 95% CI, 2.37-13.36), pneumomediastinum (P = 0.041, OR = 11.02, 95%CI, 1.10-110.54), Gottron's papules (P = 0.010, OR = 3.24, 95%CI, 1.32-7.97), and elevated erythrocyte sedimentation rate (ESR) (P = 0.005, OR = 9.9, 95%CI 2.0-49.0) were independent risk factors for in-hospital mortality of PM/DM patients. PM/DM patients continue to display high in-hospital mortality. Pulmonary infection is the strongest predictor of poor prognosis in PM/DM patients, followed by pneumomediastinum, Gottron's papules, and elevated ESR.